DETERMINANTS OF INDONESIAN CONVENTIONAL AND ISLAMIC BANK DEPOSITOR TRUST DURING THE COVID-19 PANDEMIC - Eko Fajar Cahyono; Lina Nugraha Rani; M. Fariz Fadillah Mardianto (Bank Indonesia, 2021)
Depositor trust plays an essential role in the banking sector. The main objective of this study is to test several factors that significantly affect depositors’ confidence in conventional and Islamic banks in Indonesia during the COVID-19 pandemic. We conducted qualitative research with a sample of 217 customers who had a minimum of two bank accounts, one conventional, and one Islamic. In a questionnaire, customers were asked their opinions related to indicators of the variables studied, such as depositor trust, and their perceptions of inflation, conventional bank interest, the equivalent yield rate of Islamic banks, and industry perception Productivity Index. The results of the questionnaire were analysed using the partial least squares (PLS) method. The PLS analysis results show that the indicators related to conventional bank interest and the equivalent yield rate of Islamic banks significantly affected depositors’ trust and hands. In other words, customers were influenced when making bank deposits by the factors related to conventional bank interest and the equivalent yield rate of Islamic banks. The external aspect of the industrial production index based on the PLS test had a significant effect on depositors’ trust in both types of bank. In contrast, the external factor of inflation did not significantly affect depositors’ trust in either conventional or Islamic banks. Therefore, based on the PLS-SEM results, conclusions can be drawn regarding the factors influencing depositor trust.